Physical Activity in Control of Diabetes Mellitus: An Underrated Entity - Vinoth Chellaiyan Devanbu; Aarthy Arumugam; Suruliraman SM (Medsci Publications, 2023)
Glycaemic control and reduction in mortality among diabetes can be easily achieved by a cost-effective intervention, Physical activity. Moderate to vigorous intensity activities are usually recommended for diabetics. Structured engagement of diabetes by combining physical activity and modest weight loss activities their risk can be reduced by 58%. But most of the diabetics prefer to remain inactive. Hence this article highlights the importance of physical activity, acute and chronic effects of physical activity on diabetics, recommended level of activity, recommended type of activity and ways to adhere and maintain those activities.